Effect of post length on endodontically treated teeth: fracture resistance - Jefferson Ricardo Pereira; Accácio Lins do Valle; Talita Magro Juvêncio; Janaina Salomon Ghizoni; Marcus Vinícius de Reis Só (Universidade Estadual de Campinas, 2015)
Aim: This study compared the fracture resistance of endodontically treated teeth restored with posts and cores systems with different post lengths. Methods: Sixty extracted intact canines were randomly divided in 6 groups of 10 teeth each, as follows: groups 1, 2 and 3 were restored with custom cast post-and-core, and groups 4, 5 and 6 were restored with prefabricated post and composite resin core, with different post lengths (5.0, 7.5 and 10 mm, respectively). A compressive load was applied at a 45-degree angle to the long axis until failure occurred. Results: Two-way analysis of variance (á=0.05) showed statistically significant difference between the groups (p<0.001). However, when the mean fracture forces for the groups were compared (group 1: 254.4 N; groups 2, 3, 4, 5, 6 - 331.7 N, 434.7 N, 405.4 N, 395.6 N and 393.8 N, respectively), no significant differences could be detected among the three groups restored with prefabricated post and group 3. Conclusions: This study showed that an increased post length in teeth restored with prefabricated posts does not significantly increase the fracture resistance of endodontically treated teeth. On the other hand, endodontically treated teeth restored with custom cast-post and core showed significant increase on fracture resistance when the post length is increased.